Impact of Constitutional Court Decree Number 46/PUU-VII/2010 on marriage registration - Aminah Aminah (International Journal of Sharia Studies, 2023)
Indonesia is a country with a majority Muslim population. Consequently, in matters regarding marriage arrangements, especially marriage, many laws and regulations regulate them. One of the issues regulated in statutory regulations is regarding marriage registration. Marriage registration is not regulated in Law Number 1 of 1974, which is also the source of law for other laws and regulations regarding marriage registration. The purpose of writing this article is to determine the validity of marriages that were not registered after the Constitutional Court Decision Number 46/PUU-VIII/2010, as well as to analyze the legal consequences of marriages that were not registered. Based on an analysis of the legal materials obtained, marriages not registered after a Constitutional Court Decision are valid as long as they fulfil the requirements and harmony of a valid marriage. A marriage that is not registered also has legal consequences for the status of the wife, the position of the children, and joint assets (gono-gini) in the marriage